Principles of Food Processing - Heldman, Dennis R. (Food science texts series., 1997)
This book focuses on the most common unit operations utilized in modern food processing operations. It contains both descriptive and quantitative analysis of the typical food processes found in modern food processing plants. The descriptive information provides students with background on the process and the impact of the process on food product quality. The quantitative description assists the student in understanding the ability of the process to achieve the desired result and the consequences of improper operation of the process. Examples utilizing different food commodities are incorporated to ensure that the student gains an appreciation of the relationship between commodities and processes.